Futures of privacy protection: A framework for creating scenarios of institutional change. - Minkkinen, Matti (Futures, 2015)
The future of privacy is a topical issue in the context of debates on mass surveillance and the increasing prevalence of social media sites in everyday life. Previous scenario studies on privacy have focused on macro trends and on forecasting technological developments, and claims about causal influences have remained implicit. This article presents an alternative approach for constructing scenarios of privacy protection. The article focuses on privacy protection as a social institution and builds on the theory of gradual institutional change. The article presents a scenario framework which includes three stages: (1) outlining the dynamics of privacy protection, (2) tracing historical processes and constructing a causal narrative, and (3) creating event-based scenarios. The resulting scenarios are narratives of plausible chains of events which are based on the results of the previous stages. The key difference to typical scenario approaches is the focus on specific actors and types of event sequences in privacy protection. The argument is that by lowering the level of abstraction in this way, researchers and decision-makers can gain a more profound understanding of possible future challenges in privacy protection and of key leverage points in the institutional change process.